Scanning Electron Microscopy and X-ray Microanalysis Third Edition - Goldstein, Joseph I.; Newbury, Dale E.; Echlin, Patrick; Joy, David C. (Springer US, 2003)
In the decade since the publication of the second edition of Scanning Electron Microscopy and X-Ray Microanalysis, there has been a great expansion in the capabilities of the basic scanning electron microscope (SEM) and the x-ray spectrometers. The emergence of the variab- pressure/environmental SEM has enabled the observation of samples c- taining water or other liquids or vapor and has allowed for an entirely new class of dynamic experiments, that of direct observation of che- cal reactions in situ. Critical advances in electron detector technology and computer-aided analysis have enabled structural (crystallographic) analysis of specimens at the micrometer scale through electron backscatter diffr- tion (EBSD). Low-voltage operation below 5 kV has improved x-ray spatial resolution by more than an order of magnitude and provided an effective route to minimizing sample charging. High-resolution imaging has cont- ued to develop with a more thorough understanding of how secondary el- trons are generated. The ?eld emission gun SEM, with its high brightness, advanced electron optics, which minimizes lens aberrations to yield an - fective nanometer-scale beam, and "through-the-lens" detector to enhance the measurement of primary-beam-excited secondary electrons, has made high-resolution imaging the rule rather than the exception. Methods of x-ray analysis have evolved allowing for better measurement of specimens with complex morphology: multiple thin layers of different compositions, and rough specimens and particles. Digital mapping has transformed classic x-ray area scanning, a purely qualitative technique, into fully quantitative compositional mapping
Keywords: Materials Science; Characterization and Evaluation of Materials; Materials Science, general; Science, general; Biological Microscopy; Surfaces and Interfaces, Thin Films; Nanotechnology; Materials science; Science; Microscopy; Materials / Surfaces; Thin films